2015
DOI: 10.2106/jbjs.n.00789
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Diabetes, Obesity, and Short-Term Outcomes Among Patients Surgically Treated for Ankle Fracture

Abstract: We found that patients with concurrent diagnoses of diabetes and obesity had higher health-care utilization and costs than those with neither diagnosis or with obesity alone or diabetes alone. The delay in the diagnosis of diabetes may somewhat obscure the true effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 20 publications
2
36
1
3
Order By: Relevance
“…8,10,11,13,14,16,44 Further risk factors that may coincide with diabetes are obesity, peripheral vascular disease and smoking. 15,16 Low-energy open fractures are particularly prone to complications, with reported wound complications in up to 64% of patients, infection rates of up to 36%, subsequent below-knee amputation in up to 42% and a two-month mortality of 27%. 45 Although the studies available have low patient numbers, the impact of skin ageing in open fractures is well-recognised.…”
Section: Results and Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,11,13,14,16,44 Further risk factors that may coincide with diabetes are obesity, peripheral vascular disease and smoking. 15,16 Low-energy open fractures are particularly prone to complications, with reported wound complications in up to 64% of patients, infection rates of up to 36%, subsequent below-knee amputation in up to 42% and a two-month mortality of 27%. 45 Although the studies available have low patient numbers, the impact of skin ageing in open fractures is well-recognised.…”
Section: Results and Complicationsmentioning
confidence: 99%
“…15 Obesity has been identified as an independent risk factor for complications and poorer outcomes in both diabetics and non-diabetics. 16 …”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…This is evident in the study by Folk et al [11], wherein diabetes, smoking, and open fracture were shown to be independent and significant risk factors for wound complications after surgical stabilization of calcaneus fractures. Other authors also have emphasized the effects of peripheral neuropathy, medications, and noncompliance on prognosis in fracture treatment [4,24,26].…”
Section: Limitationsmentioning
confidence: 99%
“…Weichteilkompromittierende Frakturdislokationen und -luxationen sollten sofort reponiert werden, um einem sekundären Weichteilschaden vorzubeugen. Glucose und HbA1c bietet sich insbesondere auch für die weitere Therapie an [6,20]. Eine Reduktion von 1 % HbA1c führt zu einer geschätzten Reduktion der Komplikationsrate von 25-30 %.…”
Section: Welche Unterschiede Zum Jüngeren Patienten Bestehen Beim äLtunclassified